Role of Anatomical Structure on Yield and Quality of Bast Fiber - Maiti, Ratikanta; Satya, Pratik; Narayanan, S. S. (International Journal of Bio-resource and Stress Management, 2010)
Anatomical structure (cross-sectional area and surface structure of fiber bundle) greatly contributes to quality determination of fiber filaments. Fiber bundle with greater cross-sectional area produces coarse and strong fibers suitable for gunny bags, whereas fibers with low cross-sectional area produce fine fibers used in fabrics and finer textiles. Over-retting or under-retting will reduce fiber quality. It is difficult to assess the fiber quality if not retted properly and cannot be used in breeding process. Plant breeders may use this simple technique for genetic improvement in yield and quality of bast fiber crops (jute, kenaf, ramie and flax). The paper discusses about the anatomical techniques for use by the crop breeders for superior quality genotypes in bast fibers to help the farming community and jute industry get higher profit and superior quality fibers for various end uses.